セールロンダーネ サンチ シュウヘン ノ セッピョウガクテキ チョウサ - 本山, 秀明; モトヤマ, ヒデアキ; 東, 信彦; アズマ, ノブヒコ; 藤田, 秀二; フジタ, シュウジ; Motoyama, Hideaki; Azuma, Nobuhiko; Fujita, Shuji (1997)
P(論文) みずほ高原氷床の西に接する地域では氷床の流下は大陸の海岸に沿った山脈(Sor Rondane, Belgica and Yamato Mountains etc.)によってせき止められている。そして氷床の縁には棚氷が発達している。従って氷床の形態や流動の様子はみずほ高原とは著しく異なっている。気候変動に対する東南極氷床の応答を議論するためには, 山脈の存在が氷床の安定性にどのような影響を及ぼすのかを知る必要がある。この流域の氷床が近年の気候変動に対応して現在拡大してるのか縮小してるのか, さらに過去どのような状態であったのかを調べる目的で次のような雪氷学的調査が行われた。1) セールロンダーネ山地上流のナンセン氷原からブライド湾に沿った流線上での浅層掘削, 2) 流線上での表面流動速度, 歪量, 質量収支観測, 3) セールロンダーネ山地域の山岳氷河のモニタリング。 In the area west of Mizuho Plateau, outflow of the ice sheet is hindered by a chain of mountains (Sor Rondane, Belgica and Yamato Mountains etc.) lying along the coast of the continent and ice shelves are developing at the margin of the ice sheet. Therefore the ice sheet geomorphology and dynamical behavior in this area are quite different from those on the Mizuho Plateau. In order to describe the response of the East Antarctic ice sheet to climatic change, we need to know the influence of the presence of mountains on stability of the ice sheet. This glaciological study aims to investigate whether the ice sheet and the ice shelf in this area are now increasing or decreasing in size possibly, in response to atmospheric warming, how far this part of the ice sheet departs from a steady state, and how the influence of climatic change is left inside the ice sheet and the ice shelf. For this purpose the following studies were performed in 1988 and 1989. 1) A series of shallow drillings along a selected flow line upstream of the Sor Rondane Mountains to Breid Bay. 2) Surface flow velocity, strain and mass balance measurements on the flow line. 3) Monitoring of a valley glacier in the Sor Rondane Mountains. departmental bulletin paper